Théologie de la beauté dans les écrits de Maxime le Confesseur / The Theology of Beauty in the Writings of Maximus the Confessor - Florin Crîșmăreanu (Anastasis: Research in Medieval Culture and Art, 2018)
“We talk about Beauty each time we enjoy something for the mere fact that that something exists” (U. Eco). The odyssey of beauty has passed in time through many registers, from the ontological one to the esthetic one that is dominant nowadays; from a name associated to Divinity (Dionysius the Areopagite and Maximus the Confessor), beautiful (pulchrum) has become in Latin scholastics a transcendental (Bonaventure). In the writings of Maximus the Confessor (580-662), beauty is, on the one hand, tightly related to the affirmative way of theology, because “through the beauty and greatness of creatures it is known that God is the creator of all things” (Ambigua ad Iohannem, 10), again, on the other hand, the only one that is truly Beautiful is Christ, the One of “infinite beauty”. The famous quote of Dostoevsky, “beauty will save the world”, may be understood starting from the Patristic tradition since “the work of restauration of the entire creation made by Christ has a kalokagathic character vivid embodied in the sacramental life of the Church and culminating in the Eucharistic Liturgy” (Ioan I. Ică jr.).